Planning for large-scale wind and solar power in South Africa: Identifying cost-effective deployment strategies through spatiotemporal modelling - Kevin Ummel; Charles Fant (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
South Africa hopes to expand wind and solar power. Success depends on how and where to deploy the technologies. This study develops a 10-year database of expected power generation for these technologies across South Africa. A power system model simulates the performance of different spatial deployment strategies in 2040. The results suggest that optimization of the location and quantities of the technologies could significantly reduce the cost of greenhouse gas abatement compared to conventional approaches. The data and techniques utilize open-source satellite data and software to minimize the cost of analysis, an approach that could be translated to other contexts.
Keywords: Q40; Q42; Q47; 330; abatement cost; greenhouse gas emissions; low-carbon development; optimization; renewable energy; spatiotemporal modelling